The Policy of Non-Cash Food Aid Program (BPNT) - I Putu Cakra Putra Adnyana; Sabar Untung (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
The RASTRA Program ended in 2019 replaced by the Non-Cash Food Aid Card (BPNT). There were two important things in the BPNT program, which were free to choose the type of rice and prices that change from time to time. When the policy was not well prepared, it can trigger high prices and many speculators appeared that affected the price and stock of rice on the market. On the other hand, Bulog had prepared a change of strategy in distributing rice to the community. This certainly had a direct impact on the community or Bulog itself. So that research needs to be done with the aim to find out the benefits of the BPNT program for the community and its impact on the Bulog. The research aim was to determine the benefits of the BPNT program for the community and the impact of the program on the National Logistics Agency (Bulog). The scope of the activity was reviewing the results of studies or research related to Bulog. The data collected through deskstudy then analyzed descriptively. The government program was able to reduce the expense load of beneficiary families and provide more balanced nutrition on target, on time, increase program effectiveness and encourage financial inclusion among grassroots communities, but on the other hand during the transition period in 2019 Bulog endures losses due to the BPNT program, So we need the support from all stakeholders to solve these problems.